Identifikasi dan Sosialisasi Keselamatan & Kesehatan Kerja Bengkel Sepeda Motor di Kabupaten Banyuwangi - Rubiono, Gatut; Mukhtar, Anas (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2021)
Motorcycle workshops are a vehicle maintenance service business sector that is in great demand as the number of motorcycles increases. The technical activities of the business have potential hazards related to aspects of Occupational Safety and Health (K3). This community service activity is carried out to identify hazard risks and provide knowledge on OHS aspects in motorcycle repair shops. The activity was carried out by involving two small business partners of a motorcycle repair shop who were selected by considering the age of the owner and the location of the business. Activities are carried out with the stages of coordination, implementation and preparation of reports and publication of activities. The results of the activity show that partners really need K3 knowledge but prioritize things that are practical and easy to implement.